Peculiarities of the resettlement of the first generation offspring of the exposed Techa River population - S. A. Shalaginov; L. Yu. Krestinina; N. V. Startsev; A. V. Akleev (Радиационная гигиена)
The objective of this study was to assess main regularities of resettlement of the first generation offspring of the exposed Techa River population. In the given paper the information on places and periods of residence of the population exposed on the Techa River and their offspring, obtained from the medical-dosimetric database of the URCRM was used. Groups of the first generation offspring of exposed people living at various distances from the Techa River were identified. Main regularities of resettlement of a large group of offspring of the exposed Techa River population (26 300 persons) over the period 1950-2010 were revealed. Chelyabinsk Oblast is the main resettlement area of the first generation offspring of the exposed Techa River population. The proportion of offspring living outside of their primary resettlement area is gradually increasing. Offspring outflow from the Kurgan Oblast is greater than that from the Chelyabinsk Oblast. The main part (45.9%) of the first generation offspring of the exposed Techa River population alive as of 2010 was gathered in cities. Migration of the exposed population promoted increase in the number of marriages between exposed and unexposed persons, to the birth of offspring whose one parent (either mother or father) was exposed and led to decrease in the number of offspring whose both parents were exposed. In the current study for the first time peculiarities of resettlement of two generation of people residing on radioactively-contaminated territories, exposed people and their offspring, were compared. Marked differences in the nature of resettlement of the Techa River exposed population offspring relative to their parents were registered. Offspring migrated more frequently, which is expressed in the increase in their proportion in cities up to 45.9% as compared to that of exposed persons – 30.8% (p<0.001). At the same time the proportion of the first generation offspring of the exposed Techa River population, who reside in Techa riverside settlements, is decreasing as compared to that of the exposed persons. In contrast to first generation offspring alive as of 2010, a bigger part of deceased offspring as of 2010 (30.7%) was registered in Techa riverside villages.